2016
DOI: 10.1098/rspa.2016.0340
|View full text |Cite
|
Sign up to set email alerts
|

Rogue waves in multiphase solutions of the focusing nonlinear Schrödinger equation

Abstract: Rogue waves appearing on deep water or in optical fibres are often modelled by certain breather solutions of the focusing nonlinear Schrödinger (fNLS) equation which are referred to as solitons on finite background (SFBs). A more general modelling of rogue waves can be achieved via the consideration of multiphase, or finite-band, fNLS solutions of whom the standard SFBs and the structures forming due to their collisions represent particular, degenerate, cases. A generalized rogue wave notion then naturally ent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 35 publications
4
54
0
Order By: Relevance
“…as in physical experiments (see [6]), then M 2 exceeds the triple factor for all rogue waves constructed on Figures 5 and 7 as shown in Table 3. Thus, all rogue waves constructed here correspond to physically acceptable rogue waves on the double-periodic background.…”
Section: Rogue Wavesupporting
confidence: 73%
“…as in physical experiments (see [6]), then M 2 exceeds the triple factor for all rogue waves constructed on Figures 5 and 7 as shown in Table 3. Thus, all rogue waves constructed here correspond to physically acceptable rogue waves on the double-periodic background.…”
Section: Rogue Wavesupporting
confidence: 73%
“…The rogue waves for the focusing NLSE on the cn and dn background are obtained by combining the Darboux transformation with nonlinearization of the Lax pair [12]. Meanwhile, there are some relevant works on the rogue waves on the higher genus solutions [4], in which the analytical criterion to generalized rogue waves are obtained by the Riemann-Hilbert method. The bounded ultra-elliptic solutions for the defocusing NLSE are considered by the effective integration method [38].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that only initial perturbations of significant amplitude can contain spatially localized breathers, that is consistent with the theory suggested here (the minimal amplitude of SLCP generated by breathers is determined by the perturbation width, see the second paragraph). Meanwhile S. Randoux, P. Suret and G. El have suggested that the key role in the development of periodic perturbations should be attributed to the finite-band solutions of the NLSE [31] (see also [41]). The problems of localized and periodic condensate perturbations are complimentary and both have fundamental importance.…”
Section: Discussionmentioning
confidence: 99%